2018
DOI: 10.1159/000488733
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Dendritic Cells Attenuate Liver Injury by Modulating the Balance of Treg and Th17 Cells After Ischemia Reperfusion

Abstract: Background/Aims: The present study aimed to evaluate the effects as well as the underlying mechanisms of bone marrow-derived dendritic cells (BMDCs) and exosomes produced by BMDCs (DEXs) on hepatic ischemia-reperfusion (I/R) injury (IRI). Methods: Primary hepatocytes were isolated and used to mimic the liver IR microenvironment. BMDCs were induced and characterized both biochemically with a flow cytometer (FCM) and biophysically with a microscope. Then, we exposed BMDCs to the supernatants from primary hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Besides, the exogenous exosomes could modulate the numbers of Treg and Th17 cells. Zheng et al found that exosomes produced by bone marrow‐derived dendritic cells alleviated liver I/R injury via upregulating the differentiation of Treg cells and inhibiting the differentiation of Th17 cells . In the present study, hUCB‐MSCs‐derived exosomes in the post‐I/R hepatocyte microenvironment activated naïve T cells and accelerated differentiation of Treg cells and inhibited the differentiation of Th17 cells, thereby regulating ROR‐γt, Foxp3, and Th17/Treg‐related cytokines.…”
Section: Discussionsupporting
confidence: 57%
“…Besides, the exogenous exosomes could modulate the numbers of Treg and Th17 cells. Zheng et al found that exosomes produced by bone marrow‐derived dendritic cells alleviated liver I/R injury via upregulating the differentiation of Treg cells and inhibiting the differentiation of Th17 cells . In the present study, hUCB‐MSCs‐derived exosomes in the post‐I/R hepatocyte microenvironment activated naïve T cells and accelerated differentiation of Treg cells and inhibited the differentiation of Th17 cells, thereby regulating ROR‐γt, Foxp3, and Th17/Treg‐related cytokines.…”
Section: Discussionsupporting
confidence: 57%
“…In our previous studies, pretreatment with iTregs ameliorated HIRI and decreased IFN-γ and IL-17 in the liver after reperfusion. Recently, Zheng et al found that exosomes produced by bone marrow-derived dendritic cells alleviate HIRI via regulating the balance between Tregs and Th17 cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…22 Tregs are the most important immune regulatory cells in peripheral blood, and suppress immune responses through two mechanisms: (i) Tregs express immunosuppressive molecules (HLA-G and CTLA-4) that can inhibit inflammatory cells through direct cell contact, and (ii) Tregs can secrete large amounts of IL-10 and TGF-b to inhibit inflammation and promote the proliferation the activities of other types of regulatory immune cells. 23,24 Our study found that the immunoregulatory functions of Tregs in control and LIRI mice were similar, suggesting that LIRI had no significant effect on Treg function.…”
Section: Discussionmentioning
confidence: 68%